Sex-selective abortions and infant mortality in India: the role of parents’ stated son preference - Robitaille, Marie-Claire; Chatterjee, Ishita (Taylor & Francis, 2018)
In India, millions of female foetuses have been aborted since the 1980s alongside an abnormally high infant girl mortality rate; this has generated a vast literature exploring the root causes of son preference. The literature is sparse, however, on how the decisions to abort or neglect girls are made. This paper examines mothers’ and fathers’ respective roles behind those decisions. Using NFHS-3 data, we show that sex- selective abortions are most commonly used if both spouses or if only the fathers prefer sons, while sex-selective neglect is used if only the mothers prefer sons.